Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian di Kierantea Tea & Coffee House Binjai - Pasaribu, Bonardo; Abdina, Muhammad Fadly (Universitas Medan Area, 2025)
This study aims to determine the effect of price and product quality on purchasing decisions at Kierantea Tea Coffee House. This research method uses mixed methods (qualitative and quantitative research). The results of this study indicate that price has a positive and significant effect on purchasing decisions with a Thitung Ttabel value of 3,344 2,011 and a significance value of 0.002 0.05, product quality has a positive and significant effect on purchasing decisions with a Thitung Ttabel value of 4,100 2,011, a significance value of 0.001 0.05, and simultaneously price and product quality have a positive and significant effect on purchasing decisions by 72.3% and the rest is influenced by other factors.